THE PRONOUN: ITS STRUCTURAL AND SEMANTIC TYPES, THE THEORY OF ITS GRAMMATICAL CATEGORIES (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
This article provides a comprehensive exploration of pronouns, examining their structural and semantic types, as well as the theory of their grammatical categories. It begins by categorizing pronouns based on their syntactic roles, including personal, demonstrative, interrogative, relative, reflexive, possessive, indefinite, and reciprocal pronouns. Each type is explained with examples to highlight its function and usage in language. The article then